2010
DOI: 10.1111/j.1365-2672.2010.04855.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic (EPEC), enterohaemorragic (EHEC) and verotoxigenic (VTEC) Escherichia coli in wild cervids

Abstract: Aims:  The aim of this study was to investigate the presence of enteropathogenic (EPEC), enterohaemorragic (EHEC) and verotoxigenic (VTEC) Escherichia coli strains in free‐ranging wild ruminants in Belgium and to characterize the positive isolates (serogroups and virulence‐associated factor‐encoding genes). Methods and Results:  Escherichia coli strains isolated from faeces of wild cervids were characterized by PCR targeting genes coding for the main virulence properties of EPEC, EHEC and VTEC strains. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
22
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 47 publications
8
22
5
Order By: Relevance
“…In contrast the ehxA gene was found in high prevalence (46%). These results are in agreement with previous studies on STEC isolates from wild ruminants (Gilbreath et al, 2009;Sánchez et al, 2009;Bardiau et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast the ehxA gene was found in high prevalence (46%). These results are in agreement with previous studies on STEC isolates from wild ruminants (Gilbreath et al, 2009;Sánchez et al, 2009;Bardiau et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…In STEC strains characterized in this study, stx2 was the predominant stx gene identified, a result which is in agreement with previous studies on STEC isolates from wild ruminants (Sanchez et al, 2009;Bardiau et al, 2010;Kistler et al, 2011) or isolates from game meat (Miko et al, 2009). With respect to the stx subtypes (according to the established new Stx nomenclature) (Persson et al, 2007), stx2b was the predominant variant among the STEC isolates in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Few studies have indicated the presence of virulence genes in wild animals4041. Cabal et al 42 compared the virulence gene profile of E. coli isolated from cattle, swine and broiler.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low STEC prevalences of 0.2% were reported in hunter-harvested captive deer in Louisiana (63) and 3.3% in farm-raised deer in Ohio (64). Other species of deer, including red deer (Cervus elaphus), fallow deer (Dama dama), and roe deer (Capreolus capreolus), have also been identified as capable of shedding STEC serotypes (65,66). Almost 50% of Pennsylvanian white-tailed deer fecal samples screened tested positive for stx genes; however, only 8% possessed the eae gene, which is necessary for colonization of the human intestine (67).…”
Section: Deermentioning
confidence: 99%